Primary Mucinous Adenocarcinoma of the Urinary Bladder with Signet-Ring Cells: Description of an Uncommon Case and Critical Points in Its Management - Fabrizio Di Maida; Giuliano Amorim Aita; Daniele Amorim Aita (Case Reports in Urology)
We present an uncommon case of mucinous adenocarcinoma of the bladder (MAB) with signet-ring cells extensively infiltrating prostate gland and pelvic/retroperitoneal lymph node stations and not responsive to usual systemic chemotherapy regimens. This case highlights the important features of MAB including the pattern of tumor spread, the tendency for initial misdiagnosis, and the importance of immunohistochemical study in order to define its primary origin from the bladder and choose the most appropriate treatment since the beginning.